Scheduling Of Ukm (Unit Kegiatan Mahasiswa) Sports Activities At State University Of Medan (Unimed) Using Genetic Algorithm - Yanty Faradillah (Politeknik Negeri Semarang, 2018)
Scheduling is a complex and time-consuming process, and there are many things to be adjusted. Therefore, the conventional scheduling can be completed by using the Genetic Algorithm method. This research is to solve the problem of scheduling on the activities of UKM (Unit Kegiatan Mahasiswa)//Student Activity Unit) Sport at Unimed, by using the search technique simultaneously on a number of solutions that might be known as population term. Individuals which exist in one individual population contained in one population are called chromosomes. This chromosome is a solution that is still a symbol. The initial population is randomly constructed, while the population is the result of the evolution of chromosomes through literacy called generation. Using this Genetic Algorithm scheduling plan would bring benefits to the user because scheduling can be seen on the computer and in preparing of the next schedule, there won’t be a problem or conflict.